Pembukaan Hubungan Diplomatik Uni Emirat Arab Dengan Israel Tahun 2020 - Martin, Ali; Kumalasari, Alza Agustin Tri (Kajian Hubungan Internasional, 2024)
A country's diplomatic relations with other countries are carried out with the aim of meeting the needs of each country concerned. Therefore, a country will definitely open diplomatic relations as a form of recognition of sovereignty and good relations with other countries with the ultimate aim of meeting the needs of each country. The focus of this research is on the issue of opening diplomatic relations by the United Arab Emirates towards Israel, which received a lot of rejection and opposition from other countries, especially in the Arabian peninsula countries. However, the United Arab Emirates has other considerations so the decision to open diplomatic relations with Israel remains pending. By using the theory of national interest which refers to realism, the author will connect and analyze the reasons and factors behind this policy termination. The research method in this writing uses a qualitative descriptive method, to describe in more depth the interests of the United Arab Emirates in diplomatic relations with Israel. Keywords: diplomatic relations, national interests, United Arab Emirates, Israel